Molecular phylogeny, radiation patterns and evolution of life-history traits in Ursinia (Anthemideae, Asteraceae) - Swelankomo, Nonkululeko (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Botany and Zoology))--Stellenbosch University, 2008.